An experimental investigation of shear-transfer strength of normal and high strength self compacting concrete. (15th February 2016) - Rahal, K.N.; Khaleefi, A.L.; Al-Sanee, A.
Highlights: Shear-transfer behavior of self-consolidating concrete was investigated. Specimens with clamping steel resisted large residual strength and shear slip. High-strength concrete increased ultimate but had limited effect on residual strength. Ultimate and residual strengths were checked against calculations of existing models. A simple equation for residual strength is proposed. Abstract: Fifteen non-precracked pushoff specimens were tested to investigate the shear-transfer behavior of normal strength and high strength self-compacting concrete (SCC). The reported results include the cracking stresses, the yielding stresses, the ultimate strengths and the post-ultimate residual strengths. It is shown that the specimens resisted significant post-ultimate residual strengths and shear slip values reaching 20 mm. It is also shown that increasing the compressive strength of the concrete significantly increased the ultimate shear strength but had a limited effect on the cracking and the residual strengths. The calculations of four existing models are compared with the observed ultimate strengths, and the calculated strengths are generally conservative. The AASHTO shear-friction and the SMCS models provide the best correlation with the experimental results. The possibility of using existing models to calculate the residual strength is also investigated. The shear transfer planes are assumed to be precracked, and the roughness conditions are selected based on the expected path of the cracks relative to the coarse aggregates. Eurocode 2 (EC2) provides the best correlations while the ACI calculations are generally conservative. The residual strengths from 30 pushoff specimens are analyzed. A shear friction equation with a coefficient of cohesion equal to zero, a coefficient of friction equal to 1.0, and an upper limit on the stress equal to 5.5 MPa is found to provide adequate calculation of the residual strength of non-precracked pushoff specimens.